Analisis Pelatihan Reference Manager Menggunakan Mendeley Bagi Mahasiswa Universitas Trunojoyo Madura - Fadlillah, M.; Rahman, Bohri; Maula, Qurrotu Inayatil (Yayasan Arrahman Nahdlatul Wathan, 2024)
Students' abilities in writing scientific papers must continue to be improved. Utilizing a reference manager using Mendeley is one way to improve the quality of scientific writing. However, there are quite a few students who do not know and understand the optimal use of reference managers. The aim of this research is to analyze the implementation of reference manager training using Mendeley for students at Trunojoyo University, Madura. The method used is descriptive qualitative by observing training on the use of reference managers in the form of Mendeley for writing student final assignments. The results of this research show that students have different abilities in using Mendeley for writing final assignments. There are some students who already have Mendeley accounts and software. With reference manager training, students are expected to be able to write their final assignments well and with quality.